Factors influencing the responsible innovation process: an overview on Latin America and the 20 most innovative countries - Negri Pagani, Regina (2023)
The topic innovation has been discussed in the literature for several decades. It was only after the mid-20th century that innovation became a widely recognized concept in the field of economics and management. Nowadays, the topic has become an important one not for academicians, but also to company and governments, once its outcomes are drivers for competitive advantage. The Sustainable Development Goals has been a call from the United Nations, and they should be a guideline to all the innovation processes for responsible innovation. The purpose of this paper is to explore the concept of innovation and its importance in driving progress and economic development for countries, as well as its impacts on the SDG, analyzing the factors that influences its process. In order to reach this purpose, the paper explores the Global Innovation Index (GII), an annual report that assesses the innovation capabilities and performance of the countries around the world, making a comparison with the 20 top most innovative countries in the world. The analysis of its of influencer were built from other index, and factors like Human Freedom, Corruption, and Expenditure in Education, among others, were considered. The results show the process of innovation is quite more complex, and some general assumptions cannot be made. It is required a deeper approach, including aspects mentioned along the paper. Promoting a sustained and inclusive economic development is a great challenge for countries in Latin America, and it is necessary to address some challenges, and work towards building more diversified, innovative, and competitive economies.